Relapse of Pheochromocytoma with Hipertensive Heart Disease Mildly Reduced Left Ventricle Ejection Fraction - Filianty Sipayung, Merylla; Kusnadi, Yulianto; Shahab, Alwi; Maila Dewi, Ratna; Soleh, Imran; Pramudhya Hoesain, Fadil (Journal of World Science, 2023)
Pheochromocytoma is a tumor originating from the medulla of the adrenal gland. This tumor is rare and is caused by excessive production of catecholamines. There are three classic triads of pheochromocytoma: diaphoresis, palpitations and headaches. Elevated metanephrines and normetanephrine in plasma or urine confirm the diagnosis. At the same time, radiological examination helps in the tumor's location and the presence of local invasion or metastasis. Hypertension is a health problem that is quite dangerous worldwide because it is a significant risk factor for cardiovascular diseases such as heart attack, heart failure, stroke, and kidney disease. Hypertension can cause Hypertensive Heart Disease, which is a significant cause of morbidity and mortality due to cardiovascular disease. This scientific report presents a case study of a 19-year-old woman diagnosed with relapsed pheochromocytoma and hypertensive heart disease with mildly reduced left ventricular ejection fraction. This patient was previously diagnosed at the age of 13 with pheochromocytoma, where the patient experienced symptoms of headache, sweating, especially in the forehead area, trembling hands, and hypertension. Hence, the patient had to be treated. The patient underwent further examination and found a right adrenal tumor, so an adrenalectomy was performed on the patient. Similar complaints appeared again in the patient, and further examination was carried out. Moreover, an increase in plasma metanephrine and normetanephrine levels was found. A CT scan of the abdomen revealed a right adrenal tumor, so this patient underwent another adrenalectomy.